2017
DOI: 10.1016/s2213-8587(17)30104-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive glucose control on microvascular outcomes in patients with type 2 diabetes: a meta-analysis of individual participant data from randomised controlled trials

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
305
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(332 citation statements)
references
References 18 publications
10
305
0
17
Order By: Relevance
“…Although pleiotropic effects have been inferred, improved glycemic control, lowering of blood pressure, decrease in intraglomerular pressure, reduction in albuminuria, and amelioration of volume overload are all plausible protective mechanisms. 4,[13][14][15][16][17][18][19][20][21][22][23] The effects on cardiovascular and renal outcomes observed within this program of two integrated trials are similar to those observed previously with this drug class. 5,6 The favorable direction of effect with respect to stroke observed in this trial program differs from a previously reported possible adverse effect on stroke risk.…”
Section: Placebo Better Canagliflozin Bettersupporting
confidence: 63%
“…Although pleiotropic effects have been inferred, improved glycemic control, lowering of blood pressure, decrease in intraglomerular pressure, reduction in albuminuria, and amelioration of volume overload are all plausible protective mechanisms. 4,[13][14][15][16][17][18][19][20][21][22][23] The effects on cardiovascular and renal outcomes observed within this program of two integrated trials are similar to those observed previously with this drug class. 5,6 The favorable direction of effect with respect to stroke observed in this trial program differs from a previously reported possible adverse effect on stroke risk.…”
Section: Placebo Better Canagliflozin Bettersupporting
confidence: 63%
“…11 Reduced cardiac events have also been observed in patients with type 2 diabetes after bariatric surgery. 12 In contrast, some drug trials have indicated increased mortality when HbA 1c approaches normal levels, probably through hypoglycaemia provoking arrhythmias. 13 Look AHEAD, a trial of lifestyle intervention in patients with mean diabetes duration of five years, reported 11.5% remission at 12 months with 8.6% weight loss, but that proportion fell by about 30% annually.…”
Section: Potential Metabolic Value Of Remissionmentioning
confidence: 99%
“…The absence of clear evidence for an effect differs from the absence of an effect, especially given the potential for large benefits as reported by the Diabetes Control and Complications Trial (DCCT), the United Kingdom Prospective Diabetes Study (UKPDS) and the Action in Diabetes and Vascular Disease Preteraaax and Diamicron Controlled Evaluation (ADVANCE) trial and their long-term post-trial follow-ups 1–4. Supporting this is a recent meta-analysis of individual participant data from the UKPDS, Veteran Affairs Diabetes Trial (VADT), Action to Control Cardiovascular Risk in Diabetes (ACCORD) and ADVANCE trials, reporting that intensive control resulted in a 20% risk reduction for the composite of ESKD, renal death and development of an estimated GFR (eGFR) <30 mL/min or macroalbuminuria 5. Given the rarity of and the time taken to develop ESKD, trials with longer term follow-up or conducted with high-risk groups are warranted.…”
Section: Commentarymentioning
confidence: 99%